Pengaruh Corporate Social Responsibility dan Komisaris Independen terhadap Agresivitas Pajak - Yanti Nova Lita Simorangkir; Bambang Subroto; Wuryan Andayani (University of Merdeka Malang, 2018)
This study aims to determine the effect of the corporate sosial responsibility and independent commissioners on tax aggressiveness. This study are conducted on 130 firm-years manufacturing firms listed in the Indonesian Stock Exchange during period of 2012 to 2016, selected based on purposive sampling method. Tax aggressiveness is proxy by ETR. Corporate social responsibility activities measured based on disclosures referring to Gobal Reporting Initiative (GRI) guideline. Independent commissioner is the proportion of independent commissioner in the board of commissioners. The results show that: 1) tax aggressiveness can be suppressed by the increasing activity of corporate social responsibility, 2) tax aggressiveness is not influenced by independent commissioners in the company. https://doi.org/10.26905/jmdk.v6i2.2277